A predictive biomarker for altered 5‐fluorouracil pharmacokinetics following repeated administration in a rat model of colorectal cancer. (12th August 2013) - Kobuchi, Shinji; Kuwano, Shota; Imoto, Kazuki; Okada, Kae; Nishimura, Asako; Ito, Yukako; Shibata, Nobuhito; Takada, Kanji
ABSTRACT The relationship between the plasma ratio of dihydrouracil/uracil (UH2/Ura) and hepatic dihydropyrimidine dehydrogenase (DPD) activity after repeated 5‐fluorouracil (5‐FU) treatment in rats with colorectal cancer (CRC) was investigated. Repeated intravenous 5‐FU bolus injections resulted in a significant decrease in the total clearance (CLtot) and an increased area under the curve (AUC0‐∞) in CRC rats. Furthermore, the hepatic DPD levels and the plasma ratio of UH2/Ura decreased significantly and lost their circadian rhythms in CRC rats treated repeatedly with 5‐FU, although significant circadian variation in the two parameters was observed in the control CRC rats. Moreover, a significant correlation was found between the plasma ratio of UH2/Ura and hepatic DPD activity in CRC rats untreated and treated with single or repeated 5‐FU administration (r2 = 0.865, p < 0.01). The ratio of UH2/Ura in plasma could be a predictive biomarker of the suppression of hepatic DPD levels during repeated 5‐FU‐based treatment. Furthermore, by plotting the observed pharmacokinetic parameters of 5‐FU against hepatic DPD activity levels predicted by the ratio of UH2/Ura in plasma, AUC0‐∞, CLtot and half‐life (t1/2) were closely linked to predicted hepatic DPD activity levels. These observations suggest that the factor that significantly influences the AUC0‐∞, CLtot and t1/2 of 5‐FU after single or repeated administration of 5‐FU is the hepatic DPD activity and it could be assessed by the ratio of UH2/Ura in plasma. Copyright © 2013 John Wiley & Sons, Ltd.